Current Trends in Early Pedagogy - Jolanta Karbowniczek; Beata Komorowska (Ignatianum University Press, 2019)
A child's education at an early school age is a major challenge, both at the individual and society levels. Its present shape is conditioned by, on the one hand, the development of science, especially psychology, pedagogy and didac- tics; on the other hand, by the changing socio-cultural, political and economicreality. These changes have established new trends in early school pedagogy. The article includes the process of reforming the school in terms of elementary education, the role and place of the teacher and student in the learning process, the objectives of early school education, the comprehensive development of the student, his activation and evaluation.